Pengaruh Green Accounting dan Kinerja Lingkungan terhadap Profitabilitas Perusahaan dalam Indeks SRI KEHATI - Ainis Sabina; Sri Hartati Setyowarni (Faculty of Social and Political Science, 2025)
The phenomenon of sustainability is currently a major concern in the business world, as there are increasing demands for companies to not only be profit-oriented but also responsible toward the environment and society. Green accounting and environmental performance are two essential elements that reflect a company’s commitment to sustainability principles. This study aims to analyze the influence of green accounting and environmental performance on the profitability of companies listed in the SRI-KEHATI Index during the 2022–2024 period. Green accounting is proxied by environmental disclosure based on the Global Reporting Initiative (GRI) Standards 2021 indicators, environmental performance is measured using the Program for Pollution Control, Evaluation, and Rating (PROPER) ranking, and profitability is measured by Return on Assets (ROA). The analytical method employed is panel data regression using the Random Effect Model (REM) approach, preceded by a series of classical assumption tests and logarithmic transformations to meet the normality assumption. The results show that, partially, neither environmental disclosure nor environmental performance significantly affects company profitability. However, simultaneously, both variables have a significant influence on profitability, supporting legitimacy theory and emphasizing the importance of integrating sustainability aspects into business strategies. These findings imply that companies and investors should pay greater attention to sustainability as part of long-term financial objectives while contributing to the development of environmental accounting literature in Indonesia.